MECHANISMS FOR IMPROVING THE PROCESSES OF SOCIAL REHABILITATION OF PEOPLE WITH ALCOHOL DEPENDENCE (World Bulletin of Social Sciences, 2022)
It was in this article that the author tried to implement mechanisms for improving the processes of social rehabilitation of people suffering from alcohol addiction. He also explained the origin of alcoholism, the concept of alcoholism and its essence, as well as the causes of its occurrence
Keywords: rehabilitation; adaptation; alcoholism; social causes of alcoholis